Gene Co-expression Network Analysis of the Comparative Transcriptome Identifies Hub Genes Associated With Resistance to Aspergillus flavus L. in Cultivated Peanut (Arachis hypogaea L.) - Cui, Mengjie; Han, Suoyi; Wang, Du; Haider, Muhammad Salman; Guo, Junjia; Zhao, Qi; Du, Pei; Sun, Ziqi; Qi, Feiyan; Zheng, Zheng; Huang, Bingyan; Dong, Wenzhao; et al. (Frontiers in Plant Science, 2022)
Cultivated peanut (Arachis hypogaea L.), a cosmopolitan oil crop, is susceptible to a variety of pathogens, especially Aspergillus flavus L., which not only vastly reduced the peanut products quality but also seriously threaten food safety for the contamination of aflatoxin. However, the key genes related to resistance to Aspergillus flavus L. in peanuts remain unclear. This study identifies hub genes positively associated with resistance to A. flavus in two genotypes by comparative transcriptome and weighted gene co-expression network analysis (WGCNA) method. Compared with susceptible genotype (Zhonghua 12, S), the rapid response to A. flavus and quick preparation for the translation of resistance-related genes in the resistant genotype (J-11, R) may be the drivers of its high resistance. WGCNA analysis revealed that 18 genes encoding pathogenesis-related proteins (PR10), 1-aminocyclopropane-1-carboxylate oxidase (ACO1), MAPK kinase, serine/threonine kinase (STK), pattern recognition receptors (PRRs), cytochrome P450, SNARE protein SYP121, pectinesterase, phosphatidylinositol transfer protein, and pentatricopeptide repeat (PPR) protein play major and active roles in peanut resistance to A. flavus. Collectively, this study provides new insight into resistance to A. flavus by employing WGCNA, and the identification of hub resistance-responsive genes may contribute to the development of resistant cultivars by molecular-assisted breeding.